PHYTOCHEMICAL SCREENING AND IN VITRO ANTIOXIDANT ACTIVITY OF WHOLE PLANT EXTRACTS OF SESUVIUM PORTULACASTRUM L - Chintalapani, Sathvika; MS, Swathi; Narasu, Mangamoori Lakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objectives of this study are to screen the phytochemicals, estimate the content of phenolic and flavonoid compounds, and determine the antioxidant capacity of the Sesuvium portulacastrum L. (S. portulacastrum). Methods: The crude bioactives were extracted from the dried powder of S. portulacastrum in an orbital shaker using ethanol, methanol, acetone, hexane, and diethyl ether solvents. Rotaevaporator was used to concentrate the extracts. Total phenolic and flavonoid content was estimated spectrophotometrically using Folin-Ciocalteu and aluminum chloride reagents, respectively. 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2′-Azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) (ABTS), hydrogen peroxide (H2O2), and ferric reducing antioxidant power (FRAP) assays were used to determine the in vitro antioxidant capacity. Results: Phytochemical screening of the extracts showed the presence of major classes of phytochemicals. Total phenolic content (TPC) expressed as gallic acid equivalents (GAE) ranged from 14.42 (ethanol extract) to 54.05 (diethyl ether extract) mg GAE/g dry weight. Total flavonoid content expressed as quercetin equivalents (QE) ranged from 22.03 (hexane extract) to 56.70 (methanol extract) mg QE/g dry weight. Antioxidant activity determined by different assays is highest in diethyl ether extract. A positive correlation (0.7241≤ r ≥0.8419) was found between the TPC and antioxidant activity determined by DPPH, ABTS, and H2O2 scavenging assays. Furthermore, there is a strong correlation (0.722≤ r ≥0.999) between all the pairs of antioxidant assays. Conclusion: Diethyl ether extract showed the highest TPC and antioxidant potential among all the extracts of S. portulacastrum. Further research has to be done to isolate the pure bioactive compound that has high antioxidant potential.